Investigation of antimicrobial effects of treated Lucilia sericata larvae extract on bacteria - Kaihanfar, Maryam (Iran J Microbiol, 2018)
BACKGROUND AND OBJECTIVES: Larval therapy refers to the use of Lucilia sericata larvae on chronic wounds, which is a successful method of chronic wounds treatment. The secretions of these larvae contain antibacterial compounds and lead to death or inhibition of bacterial growth. MATERIALS AND METHODS: In this study, we investigated the antibacterial effects of Lucilia sericata larvae secretions which were in sterilized and multi antibiotic-resistant bacteria-treated forms on Gram-positive Bacillus subtilis bacteria and Gram-negative Escherichia coli bacteria. In the following, we evaluated changes in gene expression of lucifensin and attacin during treatment with multi antibiotic-resistant bacteria. Investigation of the antibacterial effect was carried out using optical absorption and antibiotic disk diffusion in order to study the expression of the aforementioned genes. RESULTS: The results of this study showed that E. coli-treated larvae were able to inhibit the growth of E. coli and secretions of B. subtilis-treated larvae and were also able to inhibit the growth of B. subtilis. Gene expression of antibacterial peptides in multi antibiotic-resistant bacteria-treated larvae was increased in comparison to non-treated larvae. CONCLUSION: Due to the significant antibacterial potency of bacteria-treated larvae secretions, the secretions can be a suitable candidate as a drug against antibiotic resistant bacteria, but additional tests are required. Since the antimicrobial peptides of insects have not yet produced any resistance in human pathogenic bacteria, they can be considered as a promising strategy for dealing with resistant infections.